Silver Resistance Genes Are Overrepresented among Escherichia coli Isolates with CTX-M Production - Sütterlin, Susanne (Appl Environ Microbiol, 2014)
Members of the Enterobacteriaceae with extended-spectrum beta-lactamases (ESBLs) of the CTX-M type have disseminated rapidly in recent years and have become a threat to public health. In parallel with the CTX-M type expansion, the consumption and widespread use of silver-containing products has increased. To determine the carriage rates of silver resistance genes in different Escherichia coli populations, the presence of three silver resistance genes (silE, silP, and silS) and genes encoding CTX-M-, TEM-, and SHV-type enzymes were explored in E. coli isolates of human (n = 105) and avian (n = 111) origin. The antibiotic profiles were also determined. Isolates harboring CTX-M genes were further characterized, and phenotypic silver resistance was examined. The silE gene was present in 13 of the isolates. All of them were of human origin. Eleven of these isolates harbored ESBLs of the CTX-M type (P = 0.007), and eight of them were typed as CTX-M-15 and three as CTX-M-14. None of the silE-positive isolates was related to the O25b-ST131 clone, but 10 out of 13 belonged to the ST10 or ST58 complexes. Phenotypic silver resistance (silver nitrate MIC > 512 mg/liter) was observed after silver exposure in 12 of them, and a concomitant reduced susceptibility to piperacillin-tazobactam developed in three. In conclusion, 12% of the human E. coli isolates but none of the avian isolates harbored silver resistance genes. This indicates another route for or level of silver exposure for humans than that caused by common environmental contamination. Since silE-positive isolates were significantly more often found in CTX-M-positive isolates, it is possible that silver may exert a selective pressure on CTX-M-producing E. coli isolates.